Bone marrow mesenchymal stem cells derived cytokines associated with AKT/IAPs signaling ameliorate Alzheimer’s disease development - Yalan Lu; Yanfeng Xu; Li Zhou; Siyuan Wang; Yunlin Han; Kewei Wang; Chuan Qin (Stem Cell Research & Therapy)
Abstract Background Alzheimer’s disease (AD) is a progressive neurodegenerative condition affecting around 50 million people worldwide. Bone marrow-derived mesenchymal stem cells (BMMSCs) have emerged as a promising source for cellular therapy due to their ability to differentiate into multiple cell types and their paracrine effects. However, the direct injection of BMMSCs can lead to potential unpredictable impairments, prompting a renewed interest in their paracrine effects for AD treatment. The specific mechanism and central role of cytokines in this process have not been fully elucidated. Methods Mouse BMMSCs were isolated, validated, and then transplanted intracerebrally into APP/PS1 female mice. The behavioral tests, including open-field test, novel object recognition test, and Morris water maze were performed, followed by β-amyloidosis plaque and neuron apoptosis analyses. Then the tissue RNA sequencing and mBMMSC cytokine analysis were performed. A cytokine antibody array for BMMSCs and the brain slice models were performed with AD model tissues were used to elucidate the molecular mechanisms. Finally, APP/PS1 mice were administrated with cytokine mixture for cognitive recovery. Results Our results demonstrated that BMMSCs significantly improved cognitive function, reduced beta-amyloid plaque deposition, and decreased apoptotic neurons through the activation of the AKT signaling pathway. Using a cytokine antibody array, we identified three highly expressed AKT pathway regulated neuroprotective factors in BMMSCs: IGF1, VEGF, and Periostin2. These cytokines were found to upregulate inhibitors of apoptosis family proteins (IAPs) and suppress Caspase-3 activity in brain slices induced with beta amyloidosis (Aβ), okadaic acid (OA), and lipopolysaccharide (LPS). When injection of this cytokine mixture to APP/PS1 mice also resulted in a mitigation of cognitive impairment. Conclusions These findings suggest that the secretory factors IGF1, VEGF, and Periostin2 derived from BMMSCs play a crucial role in neuroprotection by modulating the AKT/IAPs pathway to restore neuronal function. These cytokine sets could be a potential therapeutic strategy for AD and lay the groundwork for promising clinical applications.